Simulation of rafting type and stress distribution in nickel-based superalloys with different volume fractions of γ′ phase. (3rd May 2016) - Wang, X. M.; Cao, M. Y.; Li, S. W.; Deng, C. H.; Yue, Z. F.
Abstract : A representative volume element is introduced to represent the microstructure of γ / γ ′ morphology with periodic boundary conditions to formulate the full mode of the micromechanical analysis. [0 0 1]-oriented alloys with γ ′ volume fractions from 60 to 70% are simulated under tensile loading. A raft criterion is implemented into the user subroutine to predict the rafting type. The misfit stress is considered by different thermal expansion coefficients of the two phases. It is very high in γ phase and slightly decreases with the increasing of γ ′ volume fraction. The stress distributions in the two phases change during creep deformation. The creep crack initiation time slightly increases with the increase of γ ′ volume fraction. The stress components decrease with the increasing of γ ′ volume fraction at the beginning and change due to the stress redistribution during creep loading.